A simplified PDMS microfluidic device with a built‐in suction actuator for rapid production of monodisperse water‐in‐oil droplets. Issue 24 (29th September 2020) - Nakatani, Masaya; Tanaka, Yugo; Okayama, Shotaro; Hashimoto, Masahiko
Abstract: We previously established an automatic droplet‐creation technique that only required air evacuation of a PDMS microfluidic device prior to use. Although the rate of droplet production with this technique was originally slow (∼10 droplets per second), this was greatly improved (∼470 droplets per second) in our recent study by remodeling the original device configuration. This improvement was realized by the addition of a degassed PDMS layer with a large surface area‐to‐volume ratio that served as a powerful vacuum generator. However, the incorporation of the additional PDMS layer (which was separate from the microfluidic PDMS layer itself) into the device required reversible bonding of five different layers. In the current study, we aimed to simplify the device architecture by reducing the number of constituent layers for enhancing usability of this microfluidic droplet generator while retaining its rapid production rate. The new device consisted of three layers. This comprised a degassed PDMS slab with microfluidic channels on one surface and tens of thousands of vacuum‐generating micropillars on the other surface, which was simply sandwiched by PMMA layers. Despite its simplified configuration, this new device created monodisperse droplets at an even faster rate (>1000 droplets per second).